2008
DOI: 10.1039/b718212k
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculation within grooved substrates regulates cell positioning and cell docking inside microfluidic channels

Abstract: Immobilization of cells inside microfluidic devices is a promising approach for enabling studies related to drug screening and cell biology. Despite extensive studies in using grooved substrates for immobilizing cells inside channels, a systematic study of the effects of various parameters that influence cell docking and retention within grooved substrates has not been performed. We demonstrate using computational simulations that the fluid dynamic environment within microgrooves significantly varies with groo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 44 publications
6
79
0
Order By: Relevance
“…Recently this approach has been extended and applied to a multi-level stacked substrate, radial flow bioreactor (Park et al, 2008). Recently, it was also demonstrated that the fluid dynamic environment within microgrooves, which varies with groove width, can affect cell localization and retention following cell seeding and prior to their adhesion and culture (Manbachi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Recently this approach has been extended and applied to a multi-level stacked substrate, radial flow bioreactor (Park et al, 2008). Recently, it was also demonstrated that the fluid dynamic environment within microgrooves, which varies with groove width, can affect cell localization and retention following cell seeding and prior to their adhesion and culture (Manbachi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…First examples of such manipulation harnessed capillary effect, however the development of microfabrication technologies enabled more sophisticated ways of hydrodynamic manipulation of cells and fluid flow. As an example, cells could be aligned to a single line by using sheath flow, this technique is one of many alternative hydrodynamic focusing techniques [1,2].…”
Section: Open Accessmentioning
confidence: 99%
“…The depressed trenches and microtraps serve to shield the cells from flow-induced shear stresses (Figure 1(b)). 48 The perfusion layer consists of one focal channel, adjacent to which are two flanking channels which drive flow into an open chamber containing the cells, and apposed on the other side of the open chamber by a vacuum channel which aspirates the flow (Figures 1(b) and 1(c)). We define the focal and flanking channel openings as "microjets," since the cross-sectional areas of these openings are much smaller than the rest of the connected fluidic channels: 20 lm  20 lm for the focal channel and 50 lm  50 lm for the flanking channel.…”
Section: A Device Overviewmentioning
confidence: 99%